Synthesis and Characterization of Some Novel Derivatives of 4-Hydroxymethylene-2-aryl-2-oxazolin-5-one as Potential Antibacterial Agents - KUMAR SINGH, VIPIN; SINGH, DAROGA (Asian Journal of Chemistry, 2010)
Derivatives of 4-hydroxymethylene-2-aryl-2-oxazolin-5-one were synthesized by the reaction of 4-(N,N-dimethyl amino methylene)-2-aryl-2-oxazolin-5-ones with sodium ethoxide in ethanol at room temperature. The synthesized compounds were characterised by elemental and spectral analysis. The antibacterial activities of synthesised compounds were screened against S. aureus and E. coli at different concentrations.